Smallscale production system of goat milk caramel in Costa Rica. - Mora Valverde, David (2012)
The aimed of this study was conduct a technicaland practical factibility study to assess and describe thepossibilities of diversifi cation of a goat milk project throughthe milk caramel production. This included the feasibilitystudy, production process and product design on a smallscale system in the province of San José, Costa Rica, inthe canton of Mora between the months of August 2009 toJanuary 2010. Data were obtained by concept of investment,production costs, and financial ratios. The project obtainedan investment of US $1360 (¢685 000*) for a processingunit with capacity of 50 liters per day. A production cost perliter of fresh milk of US$ 6,46 (¢3265) was determined, fora presentation of 275 ml and price of US$ 2,54 (¢1284). Settingan actualization rate of 12%, the projection generated anactual net value (NPV) of US$ 24 530 (¢12,388,000) (US$0,41 or ¢209 per unit sold), with an estimated life span of tenyears. An Internal Rate of Return (IRR) of 226% was alsodetermined. Regarding the annual production costs, the mostimportant item was purchase of milk, with 35% of the totalcost of production, followed by packaging (18%) and labeling(16%). The profi tability data corresponded to 17.9%.